2016
DOI: 10.3390/toxins8110342
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fusarium Mycotoxins in Cereal Crops and Processed Products (Ogi) from Nigeria

Abstract: In Nigeria, maize, sorghum, and millet are very important cash crops. They are consumed on a daily basis in different processed forms in diverse cultural backgrounds. These crops are prone to fungi infestation, and subsequently may be contaminated with mycotoxins. A total of 363 samples comprising of maize (136), sorghum (110), millet (87), and ogi (30) were collected from randomly selected markets in four agro-ecological zones in Nigeria. Samples were assessed for Fusarium mycotoxins contamination using a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 56 publications
9
54
6
1
Order By: Relevance
“…The frequency and contamination level found for the acetylated derivative of DON (3-ADON) was low, whereas no analyzed samples contained 15-ADON. Chilaka et al [11] found much higher contamination levels of DON and 3-ADON than any reported in our study.…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…The frequency and contamination level found for the acetylated derivative of DON (3-ADON) was low, whereas no analyzed samples contained 15-ADON. Chilaka et al [11] found much higher contamination levels of DON and 3-ADON than any reported in our study.…”
Section: Resultscontrasting
confidence: 70%
“…The high incidence of this toxin group observed in ogi , a maize-based product substantiates the vulnerability of the maize crops to FB producing fungi such as F. proliferatum and F. verticillioides. Additionally, the low levels of FBs observed in ogi baba as a fermented processed sorghum product also correlates well with the findings that sorghum is less susceptible to fungal infestation when compared to maize [11]. Whilst, data on the occurrence of the studied mycotoxins in ogi baba is scarce, studies from Nigeria have reported the presence of FBs in sorghum grains [11,15].…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Van sorghum in India is bekend dat tijdens de teeltperiode de schimmel Fusarium moniliforme onder bepaalde omstandigheden fumonisine als mycotoxine vormt, die ziekten bij mens en dier kan veroorzaken (Bhat et al, 1997). Ook in Nigeria werden mycotoxinen van Fusarium gevonden in sorghum, maar vergeleken met andere gewassen zoals maïs, millet en ogi, in een lagere hoeveelheid, respectievelijk 44% vs 77%, 59%, 97% (Chilaka et al, 2016). bladluis 'greenbug' en de 'sorghum mug' komen niet voor (Williams et al, 1980, De Milliano et al, 1992, Leslie, 2002, Berenji & Dahlberg, 2004.…”
Section: Ziekten En Plagenunclassified